Bioactive compounds from marine yeast inhibits lung cancer - Manikandaprabhu Sekar, Senthilraja Poomalai, Manivel Gunasekaran, Prakash Mani, Anand Krishnamurthy (Journal of Applied Pharmaceutical Science, 2015)
Anticancer agents derived from natural products such as various sources like plants, animals and microorganisms. Marine-derived microorganism has become important sources of new bioactive molecules. The products isolated from marine sources possess cytotoxic activities against many cancers. Secondary metabolites as a source of Candida albicans natural drugs many of the medicines prescribed today are natural products obtained from terrestrial plants and microorganisms. The major components (80-90%) of cell wall of are carbohydrates, mannose or polymers of mannose covalently associated with proteins to form glycoproteins. The American Cancer Society has estimated 159,260 deaths due to lung cancer from diagnosis of 224,210 new cases in the United States in 2014. The International Agency for Research on Cancer estimated over 1 million new cancers cases in India in 2012 (10, 14, 934). In this study, we aimed to find new bioactive compounds from crude culture extracts produced by C. albicans as isolated from coastal mangrove ecosystem and docking studies were carried out.
Keywords: Lung cancer, Marine Microorganism, Candida albicans, Bioactive molecules, Docking analysis.